Bronchoscopically delivered microwave ablation in an in vivo porcine lung model. Issue 4 (13th October 2020) - Sebek, Jan; Kramer, Steve; Rocha, Rob; Yu, Kun-Chang; Bortel, Radoslav; Beard, Warren L.; Biller, David S.; Hodgson, David S.; Ganta, Charan K.; Wibowo, Henky; Yee, John; Myers, Renelle; et al.
Background: Percutaneous microwave ablation is clinically used for inoperable lung tumour treatment. Delivery of microwave ablation applicators to tumour sites within lung parenchyma under virtual bronchoscopy guidance may enable ablation with reduced risk of pneumothorax, providing a minimally invasive treatment of early-stage tumours, which are increasingly detected with computed tomography (CT) screening. The objective of this study was to integrate a custom microwave ablation platform, incorporating a flexible applicator, with a clinically established virtual bronchoscopy guidance system, and to assess technical feasibility for safely creating localised thermal ablations in porcine lungs in vivo . Methods: Pre-ablation CTs of normal pigs were acquired to create a virtual model of the lungs, including airways and significant blood vessels. Virtual bronchoscopy-guided microwave ablation procedures were performed with 24–32 W power (at the applicator distal tip) delivered for 5–10 mins. A total of eight ablations were performed in three pigs. Post-treatment CT images were acquired to assess the extent of damage and ablation zones were further evaluated with viability stains and histopathologic analysis. Results: The flexible microwave applicators were delivered to ablation sites within lung parenchyma 5–24 mm from the airway wall via a tunnel created under virtual bronchoscopy guidance. No pneumothorax or significant airway bleeding was observed. The ablation short axis observed on gross pathology ranged 16.5–23.5 mm and 14–26 mm on CT imaging. Conclusion: We have demonstrated the technical feasibility for safely delivering microwave ablation in the lung parenchyma under virtual bronchoscopic guidance in an in vivo porcine lung model. This paper demonstrates the technical feasibility of safely delivering microwave ablation in the lung parenchyma under virtual bronchoscopic guidance in an in vivo porcine lung model https://bit.ly/32aruLf